(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
The contribution starting from the analytical study of five small water-stair fountains of Aquileia tries to place these pieces in the larger class of miniature fountains with steps. Their spreading, rather limited, seems to be related to a purely urban fashion, accepted in Italy only in Lazio and in Cisalpine. As an essential premise to this study there are some remarks and clarifications about the terminology, the shape, the decorations, the style and the chronology of this kind of furniture, which lay the bases for the comprehensive study of the material. The fountains with steps of Aquileia, a valid evidence of the will to adapt to the fashion of the capital, although showing the characteristics commonly found in this class of material, make it possible to find out new structural variants and to confirm or correct the dating of some formal changes noted.